Determination, diversification and multipotency of mammalian myogenic cells - MURPHY, PAULA (My University, 2008)
In amniotes, myogenic commitment appears to be dependent upon signaling from neural tube and dorsal ectoderm, that can be replaced by members of the Wnt family and by Sonic hedgehog. Once committed, myoblasts undergo different fates, in that they can differentiate immediately to form the myotome, or later to give rise to primary and secondary muscle fibers. With fiber maturation, satellite cells are first detected; these cells contribute to fiber growth and regeneration during post-natal life. We will describe recent data, mainly from our laboratory, that suggest a different origin for some of the cells that are incorporated into the muscle fibers during late development. We propose the possibility that these myogenic cells are derived from the vasculature, are multi-potent and become committed to myogenesis by local signaling, when ingressing a differentiating muscle tissue. The implications for fetal and perinatal development of the whole mesoderm will also be discussed.
PUBLISHED
Keywords: Myogenic determination; myogenic lineages; satellite cells; multipotent progenitors